An Investigation on the Formation of Carbon Nanotubes by Two-Stage Chemical Vapor Deposition. (4th April 2012) - Shamsudin, M. S.; Achoi, M. F.; Asiah, M. N.; Ismail, L. N.; Suriani, A. B.; Abdullah, S.; Yahya, S. Y. S.; Rusop, M.
Abstract : High density of carbon nanotubes (CNTs) has been synthesized from agricultural hydrocarbon: camphor oil using a one-hour synthesis time and a titanium dioxide sol gel catalyst. The pyrolysis temperature is studied in the range of 700–900 ° C at increments of 50 ° C. The synthesis process is done using a custom-made two-stage catalytic chemical vapor deposition apparatus. The CNT characteristics are investigated by field emission scanning electron microscopy and micro-Raman spectroscopy. The experimental results showed that structural properties of CNT are highly dependent on pyrolysis temperature changes.